2016
DOI: 10.1177/0886260516633217
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Prevalence, Perceived Significance, and Response to Dowry Solicitation and Domestic Violence in Bangladesh

Abstract: The current study focuses on the prevalence of two pervasive gender-related crimes in Bangladesh: dowry solicitation and domestic violence. We assess victim perceptions of how these two crimes rank in significance compared with other types of crimes experienced and the actions victim households took in response. Our research builds on prior qualitative studies by making use of nation-wide household survey data, collected by the World Bank, to examine dowry and domestic violence in the context of all legal conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(207 reference statements)
0
5
0
Order By: Relevance
“…Therefore, insults of their character and behavior may make them very emotionally vulnerable, as they may anticipate becoming victims of honor crimes. It is surprising that the men in this study did not identify honor crimes in their descriptions of abuse, despite the prevalence of these crimes in the South Asian diaspora (Mayeda et al, 2018; Verma et al, 2017; Young & Hassan, 2016). Only two previous studies investigating spousal violence in South Asian communities, both of which focused on the perspectives of female victims, have identified husbands having affairs (Abraham, 1998) and substance abuse (Hyman et al, 2011) as problems within their abusive marriages.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, insults of their character and behavior may make them very emotionally vulnerable, as they may anticipate becoming victims of honor crimes. It is surprising that the men in this study did not identify honor crimes in their descriptions of abuse, despite the prevalence of these crimes in the South Asian diaspora (Mayeda et al, 2018; Verma et al, 2017; Young & Hassan, 2016). Only two previous studies investigating spousal violence in South Asian communities, both of which focused on the perspectives of female victims, have identified husbands having affairs (Abraham, 1998) and substance abuse (Hyman et al, 2011) as problems within their abusive marriages.…”
Section: Discussionmentioning
confidence: 64%
“…These factors naturally interact, with law and policy frameworks in a world region setting the context for what becomes socially acceptable or unacceptable in one’s marriage or family life, and hence culturally reinforced through socialization and intergenerational transmission. Research findings in South Asian countries have highlighted similar variables to explain spousal violence rates, which include: (a) limited justice system/police intervention or response, as these countries have been some of the last countries in the world to ratify the United Nations Convention on the Elimination of All Forms of Violence Against Women (Ahmed-Ghosh, 2004; Akhter & Wilson, 2016); (b) different levels of social acceptability of violence against women (Boyle et al, 2009; Ler et al, 2017; Rani & Bonu, 2009); (c) unique manifestations of violence in their collectivist culture where multiple family members may support abuse of women, rather than intervene to help (Fernandez, 1997; Rastogi & Therly, 2006; Yount et al, 2016); (d) reporting barriers such as a perceived lack of support and the stigma attached to divorce (Subramaniam & Sivayogan, 2001; Young & Hassan, 2016); and (e) cultural beliefs, such as women being socialized to be subservient and to view their husband as their god (Babu & Kar, 2010; Rocca et al, 2009).…”
mentioning
confidence: 99%
“…[20] and are known to have a severely negative impact on the bride and her family members as it is strongly associated with family tensions, violence, dowry killings, and burning of brides [71]. According to the findings of a study conducted in Bangladesh, dowry culture and domestic violence are among the top five most common crimes [82]. Despite the negative impact of dowry culture, it is still being encouraged and practiced in low-income countries as families recognize positive aspects of dowry associated with women's status and decision-making power in her house [20].…”
Section: Recommendations To Avoid Dowry and Violence Practices In Pak...mentioning
confidence: 99%
“…This broader concept entails sexual abuses or assaults, acid-violence, rape, family violence, female genital mutilation, human trafficking and dowry (Baker, 2007; Chowdhury, 2007; Cole and Phillips, 2008). Different forms of GV such as rape, acid-violence, dowry, family violence and human trafficking are prevalent in Bangladesh (Anwary, 2007; Islam et al , 2021; Khan, 2015; Young and Hassan, 2016). A survey conducted by the Bangladesh Bureau of Statistics in 2015 reported that of the 19,987 married women interviewed, 49.6% had experienced physical violence and 27.3% had faced sexual violence in their lifetime (Bangladesh Bureau of Statistics, 2016).…”
Section: Introductionmentioning
confidence: 99%